Reformulating Political Party Court Procedures in Parties' Dispute Settlement - Happy Agung Saputra; Iwan Rachmad Soetijono; Shofi Munawwir Effendi (Indonesian Journal of Law and Society, 2020)
This paper aims to revisit the procedures for internal dispute resolution of political parties through political party courts. Reformulation is the stage of law enforcement in abstracto by the legislature or is limited to the formulation of provisions and substances that will be regulated in law in accordance with the situation and conditions, both present and future. The political party court is an important institution in the law enforcement process that has a mixed-function, namely as a regulator, administrator, and even adjudicator with a quasi-judicial nature. Internal dispute resolution brought to the political party court is to ensure the freedom of political parties, as well as to limit government interference which can lock in the freedom and role of political parties as one of the institutions needed to exercise people's sovereignty. Thus, it is urgent to have the idea of ​​reformulating the procedural arrangements of the political party court which are in accordance with the principles of justice and can be accounted for. This is an answer to the problems of political party disputes so that these dispute cases can be accommodated through strict and perfect regulations.KEYWORDS: Reformulation, Political Party Court, Dispute Resolution, Political Parties.